Infection prevention and control and water, sanitation, and hygiene status of healthcare facilities in the Greater Kampala Metropolitan region during the COVID-19 pandemic in Uganda - Mugambe, Richard K.; Wanyenze, Rhoda K.; Ssekamatte, Tonny; Isunju, John Bosco; Nalugya, Aisha; Wafula, Solomon T.; Musoke, David; Mukasa, Hajra Comfort; Balen, Julie; Yakubu, Habib; Moe, Christine L. (PLOS Water, 2025)
Infection Prevention and Control (IPC) and Water Sanitation and Hygiene (WASH) are critical in preventing the spread of healthcare Associated Infections, including COVID-19. However, there was limited evidence on the status of IPC/WASH in healthcare facilities (HCFs) in Uganda amidst the COVID-19 pandemic which complicated IPC/WASH planning for the COVID-19 response. This study assessed IPC/WASH status for HCFs in the Greater Kampala Metropolitan Area (GKMA), during the COVID-19 pandemic, so as to inform programming and policy. A mixed methods cross-sectional study was conducted in 75 HCFs following the first wave of COVID-19 in Uganda. The mWater tool was used to collect quantitative data which were then analyzed into STATA version 16. A key informants’ guide was used to collect qualitative data, which was analyzed thematically and themes and quotes used to support the quantitative findings. Overall, 86.7% (65/75) of HCFs had an IPC committee and 72.3% (47/65) of these were functional. Besides, 90.7% (68/75) of the HCFs had an IPC focal person, and 49.3% (37/75) had a clear annual IPC activity plan. Unfortunately, only 32.3% (21/65) of the functional IPC committees received budgetary support for their activities. In terms of WASH infrastructure, 96.0% (72/75), 10.7% (8/75), 60.0% (45/75), and 22.7% (17/75) had access to a basic water service, a basic sanitation service, a basic hand hygiene service and a basic environmental cleaning respectively. Our study reveals that while most HCFs have IPC committees and focal persons, functional support remains limited, with half having a clear annual plan and less than a third receiving budgetary support. Nearly all HCFs have basic water services, but there are significant gaps in sanitation and environmental cleanliness domains. These findings highlight the urgent need for improved support and investment in IPC/WASH supplies and infrastructure to enhance infection control and public health outcomes in Uganda. CrossRef